Public Expenditure and Financial Accountability Assessment : Greater Amman Municipality, The Hashemite Kingdom of Jordan - World Bank (World Bank, Washington, DC, 2017)
The Public Expenditure and Financial Accountability (PEFA) Program provides a framework for assessing and reporting on the strengths and weaknesses of public financial management (PFM) using quantitative indicators to measure performance. PEFA is a tool that helps governments achieve sustainable improvements in PFM practices. It does so by providing a means to measure and monitor performance against a set of indicators across the entire range of public financial management institutions, systems, and processes. The assessment provides the management of the Greater Amman Municipality (GAM) with an indicator-led assessment of the operation of the city’s PFM systems. This assessment focuses on GAM’s PFM system, according to Government Finance Statistics (GFS) from 2014. It includes cross-cutting and overall issues, revenue issues, and the budget cycle from planning through execution to control, reporting and audit. A number of indicators are designed to probe the interaction between the GAM and public service providers at the local level, including the use of extra budgetary funds. Therefore, this assessment covers the general government as applied to the GAM, including all districts and GAM-controlled funds which are accounted for separately outside of the budget.